2014
DOI: 10.1007/s13594-014-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of sodium carboxymethyl cellulose and soybean soluble polysaccharides on stability of acidified skimmed milk drinks

Abstract: Sodium carboxymethyl cellulose (CMC) and soybean soluble polysaccharide (SSPS) are negatively charged polysaccharides that are used to prevent casein aggregation in acidified skimmed milk drinks (ASMDs). The objective of this study was to examine the effect of CMC and SSPS combination on the stability of acidified skimmed milk drinks in comparison to their individual effects. Stability was evaluated based on the changes in sedimentation ratio, viscosity, zeta potential, and particle size distribution of casein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
(51 reference statements)
3
11
0
Order By: Relevance
“…The present study indicated that CMC alone (0.6% w/w) could not create an appropriate stability during the storage period. The result was in agreement with previous research by Ntazinda et al (2014). They investigated the stabilising behaviour of soybean soluble polysaccharides (SSPS) and CMC in acidified skimmed milk drinks.…”
Section: Physical Stabilitysupporting
confidence: 92%
See 4 more Smart Citations
“…The present study indicated that CMC alone (0.6% w/w) could not create an appropriate stability during the storage period. The result was in agreement with previous research by Ntazinda et al (2014). They investigated the stabilising behaviour of soybean soluble polysaccharides (SSPS) and CMC in acidified skimmed milk drinks.…”
Section: Physical Stabilitysupporting
confidence: 92%
“…The result was in agreement with previous research by Ntazinda et al . (). They investigated the stabilising behaviour of soybean soluble polysaccharides (SSPS) and CMC in acidified skimmed milk drinks.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations